Linkage between tourism and sustainable development in urban areas - Marinela Krstinić Nižić; Maša Trinajstić; Zvonimira Šverko Grdić (Ekonomski Vjesnik, 2021)
Purpose: Over the last decades, tourism has experienced continued growth, and its impact on economic activity can be observed through its effects on the balance of payments and the labour market, as well as connections with other economic activities. According to the ITB report (2016), urban tourism recorded the largest increase, noting that tourist arrivals in urban areas increased by 58% in the past five years. This was due to growing urbanization, better road accessibility and air connectivity between cities, shorter stays and an increasing number of trips per year. In recent years, the number of tourist arrivals in urban areas has also increased in Croatia. In 2018, over 12 million arrivals were recorded, which represents 64% of the total tourist arrivals for that year. Methodology: The aim of this paper is to investigate the relationship between tourism (tourism indicators) and sustainable development (investment in sustainable development) in cities in Croatia. The survey covered all 128 cities. The data analysis was conducted using descriptive analysis, correlation analysis, Mann-Whitney test and regression analysis. Results: The results show that there is a correlation between tourism and sustainable development in the analysed cities. Cities with thriving tourism pay more attention to sustainable development. Conclusion: It is necessary to continuously increase the levels of knowledge and understanding of tourism in accordance with the principles of sustainable development.